Pomoc rozwojowa dla krajów Trzeciego Świata - Rymarczyk, Jerzy (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents and evaluates the range of the Official Development Assistance imparted by nineteen developed countries of the world for the developing countries. The author analyzes the local and the trade structure of development assistance and the forms of help. He also touches on the problem of assistance coordination at the international scale. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 297-307